Data Security in Unattended Wireless Sensor Networks - Vepanjeri Lokanadha Reddy, Sasi Kiran (Université d'Ottawa / University of Ottawa, 2013)
In traditional Wireless Sensor network's (WSN's), the sink is the only unconditionally trusted authority. If the sink is not connected to the nodes for a period of time then the network is considered as unattended. In Unattended Wireless Sensor Network (UWSN), a trusted mobile sink visits each node periodically to collect data. This network differs from the traditional multi hop wireless sensor networks where the nodes close to the sink deplete their power earlier than the other nodes. An UWSN can prolong the life time of the network by saving the battery of the nodes and also it can be deployed in environments where it is not practical for the sink to be online all the time. Saving data in the memory of the nodes for a long time causes security problems due to the lack of tamper-resistant hardware. Data collected by the nodes has to be secured until the next visit of the sink. Securing the data from an adversary in UWSN is a challenging task. We present two non-cryptographic algorithms (DS-PADV and DS-RADV) to ensure data survivability in mobile UWSN. The DS-PADV protects against proactive adversary which compromises nodes before identifying its target. DS-RADV makes the network secure against reactive adversary which compromises nodes after identifying the target. We also propose a data authentication scheme against a mobile adversary trying to modify the data. The proposed data authentication scheme uses inexpensive cryptographic primitives and few message exchanges. The proposed solutions are analyzed both mathematically and using simulations proving that the proposed solutions are better than the previous ones in terms of security and communication overhead.
Keywords: Unattended wireless sensor network; Security; Proactive adversary; Reactive Adversary; Data Authentication; Data survivability; Cryptography